(untitled) (Current Problems in Rail Vehicles, 2021)
The article contains description of a mathematical model of the movement of a four-axle freight wagon on a rail track. With the help of mathematical modelling, studies of the running resistance of a wagon with wheels of various design schemes have been carried out. There are compared two wheel designs, namely the design of a traditional wheel with a monolithic production tread surface and the flange and the perspective wheel design, which allows independent rotating of support surface of the wheel and of its guiding surface, i.e. of its flange. Potential advantages of using the wheels of a perspective design scheme in a bogie of a wagon are revealed, which consist in reducing its resistance of movement.